Development of Robot Hands for Linear Parallel Pinching and Self-adaptive Grasping with Springs and Hoeckens Linkage - Yankai Liu; Wenzeng Zhang (Jixie chuandong)
Parallel pinching is an important grasping mode of robot hands. However，because the end phalange moves along the arc track，the robot hand needs the manipulator to cooperate with the lifting when pinching objects on the desktop，which increases the difficulty of grasping objects of different sizes. To solve this problem，a linear parallel pinching mode is introduced in which the end phalange is translational in a linear trajectory. Based on this model，a SHKL finger，for linear parallel pinching and adaptive grasping based on springs and Hoeckens linkage is proposed. The SHKL finger uses Hoeckens linkage to realize the linear movement of the end joint，uses double parallel four-bar linkage with the same direction and speed to realize the attitude fixation of the end phalange relative to the palm，and uses elastic joints，springs and limits to realize the self-adaptive grasping. The theoretical analysis and experimental results show that the SHKL hand has the functions of linear parallel pinching and self-adaptive grasping. Its grasping is stable and its control is easy.